Gambaran Penatalaksanaan Perawatan Bayi Prematur Di Ruang Nicu Rs. X Surabaya - Emiliana Luh Damayanti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2018)
ABSTRACT According to the data in get from hospital medical record x surabaya , number of premature as many as 76 from year 2015-2017 premature death and complication ) a number 5 cases .Premature infants at risk experienced hipotermi , asphyxia and death .The role of health workers were very helpful in the implementation of the treatment of infants premature to prevent the occurrence of complication .The purpose of this research to know the image of the treatment of infants penatalaksanaan premature ( hipotermi prevention , prevent the , providing nutrition , weighing bodies ) in the NICU x surabya hospital .Methods used in this research is descriptive , of the receipt of the data using ( observation ) primary data .Population in this research is all premature infants in january 2015 up to december 2017 in the NICU x hospital surabaya .Was used in the study included in the sampling method of accidental namely 76 premature infants .The image of the treatment of infants penatalaksanaan premature in the NICU x surabaya hospital.